The Use Of Pros In Science Learning To Improve Creativity Of Class III Students Of SD Negeri 0421 Despot Mandian - Ardani Daulay; Hasrijal Hasrijal (Indonesian Journal of Basic Education, 2022)
During the pandemic, the creativity of students and teachers in the distance learning process is highly expected to maximize teacher capacity, especially for students who need to study online, but this demand is not in Indonesia. Best applied in all schools. Students at SD Negeri 0421 Despot Mandian face obstacles for both students and teachers due to the lack of internet access and cell phone facilities. Therefore, in this study, an alternative approach that is easier to use by students and teachers is used, namely using natural material teaching aids for object motion courses using a procedural approach that requires students and teachers to be more active in mental movements. In the application, the teacher prepares media for the object of motion aids, then demonstrates and asks students what they see, then students guess (hypothesize) and present, then the teacher draws conclusions based on the theme of the object's motion material. Based on the LKS assessment of 20 students during their study period, 35% in the first cycle and 85% of the average students in the second cycle. It can be concluded that the first cycle has not achieved maximum learning outcomes because the media used is still new to them and needs to be adjusted, while in the second cycle it increases because the media used is interesting, students are used to it, so students can easily understand it